The Role of Preceptor and Knowledge of Students on Triage Skills in The Emergency Unit - Emil Huriani; Fitri Mailani; Vebby Fitri Nur’arita (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2022)
Nurse profession students are required to have skills in triage. So that when students do triage, there will be no over-triage and under-triage. This study aimed to determine the relationship between the preceptor role and knowledge of nursing profession students' perceptions of triage skills. This study was a descriptive-analytic study using a cross-sectional approach. The sampling technique used a consecutive sampling technique where the research was conducted for one month. The number of respondents in this study was 84 students of the nursing profession. Data were collected using instruments preceptor role questionnaire (PRQ), triage knowledge questionnaire (TKQ), and triage skill questionnaire (TSQ). Analysis of the research data showed that 58.3% of the students' preceptor roles were good, 53.6% had sufficient triage knowledge, and 58.3% of students perceived their triage skills to be good. There were significant correlations between the preceptor's role and expertise with the perception of triage skills of nursing profession students with a p-value <0.05. It is recommended to improve the knowledge and skills of professional nursing students through lectures on triage using a role-play or scenario learning system to enhance the knowledge and skills of triage students of the nursing profession.Keywords: triage skills; preceptor role; knowledgePeran Pembimbing dan Pengetahuan Terhadap Keterampilan Triase Mahasiswa di Instalasi Gawat DaruratABSTRAKMahasiswa program profesi ners dituntut untuk kompeten dalam melakukan keterampilan triase sehingga terhindar dari kesalahan dalam melakukan triase seperti over triage dan under triage. Tujuan penelitian ini adalah untuk mengidentifikasi hubungan peran preseptor dan pengetahuan dengan keterampilan triase pada mahasiswa program profesi ners. Desain penelitian adalah deskriptif analitik dengan pendekatan cross-sectional study. Jumlah sampel adalah 84 orang mahasiswa program profesi ners yang praktek di Instalasi Gawat Darurat salah satu rumah sakit di Kota Padang. Instrumen penelitian yang digunakan yaitu Preceptor Role Questionnaire (PRQ), Triage Knowledge Questionnaire (TKQ), dan Triage Skill Questionnaire (TSQ). Analisis statistik yang digunakan adalah uji Chi-square. Hasil penelitian menunjukkan bahwa peran preseptor baik (58,3%), pengetahuan triase cukup (53,6%), dan keterampilan triase mahasiswa baik (58,3%). Peran preseptor dan pengetahuan berhubungan dengan keterampilan triase mahasiswa program profesi ners dengan (p < 0,05). Disarankan agar institusi pendidikan menerapan metode pembelajaran role play atau skenario untuk perkuliahan mengenai triase agar dapat meningkatkan pengetahuan dan keterampilan triase mahasiswa program profesi ners. Kata Kunci: keterampilan triase, peran preseptor, pengetahuan